1993
DOI: 10.3109/03009749309099253
|View full text |Cite
|
Sign up to set email alerts
|

Longterm Physical Training in Rheumatoid Arthritis. A Randomized Trial with Different Training Programs and Blinded Observers

Abstract: The objective was to study the long-term effect (2 years) of different training programs in patients with rheumatoid arthritis. The method was a randomized trial with 75 patients participating. The measured variables included morning stiffness, a pain score, number of swollen joints, a health assessment score, a functional score, ESR, Hb, the cost of medicine, and progression using X-rays of hands and feet. The results showed no effect of training on the disease activity or on the progression of the disease. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
7

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 10 publications
0
58
0
7
Order By: Relevance
“…Hansen et al (28) found that only half of the patients who started with a 2-year exercise program attended at least 50% of the once weekly sessions, and Stenströ m et al (15) reported that 37% of patients did not complete a 1-year exercise program. We hypothesize that several aspects of the RAPIT exercise program could have contributed to the high adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al (28) found that only half of the patients who started with a 2-year exercise program attended at least 50% of the once weekly sessions, and Stenströ m et al (15) reported that 37% of patients did not complete a 1-year exercise program. We hypothesize that several aspects of the RAPIT exercise program could have contributed to the high adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Many o f the previously mentioned studies reported psychosocial benefits due to exercise in water (Bacon et al, 1991;DeVylder, 1995;Hansen et al, 1993;Minor et al, 1989;Stenstrom et al, 1991). Even more of these previously cited studies measured functional changes or discussed self-reports of increased abilities (Danneskiold et al, 1987;DeVylder, 1995;Green et al, 1993;Minor et al, 1989;Rasmussen & Hansen, 1989;Stenstrom et al, 1991).…”
Section: Esyshqsqgj^and-fynctiqdal Benefitsmentioning
confidence: 99%
“…Two studies report mixed results regarding the physical effects of aquatic exercise on persons with arthritis (Hansen, Hansen, Langgaard, & Rasmussen, 1993;Green, McKenna, Redfem, & Chamberlain, 1993).…”
Section: Studies Of Physical Effectsmentioning
confidence: 99%
See 2 more Smart Citations